Jogue com garra! estratégias pedagógicas e lúdicas para o ensino da ortografia de "g" e de "gu" nos anos iniciais do ensino fundamental - Sousa, Roseli de Oliveira (2025)
This paper presents a study that proposes reflections on the teaching and learning process of orthography, based on the diagnosis of spelling difficulties among a 4th-grade class in the Municipal School System of Aracaju – SE, specifically related to the writing of words containing the letter “g.” Linguistic research focused on the acquisition of oral and written language has significantly contributed to enabling Portuguese language teachers to understand the skills involved in learning to write. Thus, with the primary goal of developing pedagogical and playful strategies that contribute to improving students’ spelling, this study adopts, as its theoretical framework within the field of literacy, the works of Soares (2020) and Kleiman (2005). It is also grounded in the analysis by Morais (2003) on the orthographic norms of Brazilian Portuguese, particularly regarding the regularities that govern the spelling of the sounds represented by the letter “g.” In the field of linguistics, from the perspective of phonetics and orality, the study draws on the works of Seara, Nunes, and Lazzarotto-Volcão (2023), Cristófaro-Silva (2003), and Cagliari (2008), which highlight the importance of auditory experience for learners, since speech influences writing acquisition, with phonological awareness serving as a facilitating factor in this process. The study also considers contributions from grammarians such as Almeida (2009), Bechara (2015), and Cunha (2017), which are relevant to understanding the digraph “gu” in the Portuguese language. Furthermore, the study addresses historical and philological issues related to the letter “g,” the evolution and transformations of the alphabetic writing system, and the relevance of writing to human development. These reflections are based on the contributions of scholars such as Man (2002), Fischer (2009), and Cagliari (2009), who demonstrate that the development of written language was a long and gradual process. This perspective supports the understanding that improving students’ writing also requires time and continuous guidance. Based on the data collected during the initial diagnostic assessment and the theoretical foundations developed throughout the research, a pedagogical booklet was created as an intervention. This booklet comprises a sequence of activities structured around texts and the contextualization of spelling challenges. These activities suggest pedagogical and playful resources that, through the development of phonological awareness skills, support the teaching and learning of orthography. Among these resources, a game titled “Play with Grit! – The G Sound Game Board” stands out. Its aim is to promote reflection on the phonographic correspondences of the letter “g,” whether with the /g/ or /ʒ/ sound, as well as to teach the correct use of the letter “g” and the digraph “gu.” Given that this approach yielded significant results in overcoming the observed spelling difficulties and fostered student engagement in reflective language learning situations, its implementation is considered successful. Its versatility is also noteworthy, as it offers multiple possibilities for application in Portuguese language instruction, with appropriate adjustments to content and educational level, thus making it possible to teach orthography in a dynamic and motivating way.